Observations of ice nucleating particles over Southern Ocean waters - McCluskey, CS; Hill, TCJ; Humphries, RS; Rauker, AM; Sebastien Moreau; Peter Strutton; Chambers, SD; Williams, AG; McRobert, I; Ward, J; Keywood, MD; Harnwell, J; et al. (2018)
A likely important feature of the poorly understood aerosol‐cloud interactions over the Southern Ocean (SO) is the dominant role of sea spray aerosol, versus terrestrial aerosol. Ice nucleating particles (INPs), or particles required for heterogeneous ice nucleation, present over the SO have not been studied in several decades. In this study, boundary layer aerosol properties and immersion freezing INP number concentrations ( n INPs ) were measured during a ship campaign that occurred south of Australia (down to 53 °S) in March‐April 2016. Ocean surface chlorophyll‐ a concentrations ranged from 0.11‐1.77 mg m ‐3 and n INPs were a factor of 100 lower than historical surveys, ranging from 0.38 to 4.6 m ‐3 at ‐20 °C. The INP population included organic heat‐stable material, with contributions from heat‐labile material. Lower INP source potentials of SO seawater samples compared to Arctic seawater were consistent with lower ice nucleating site densities in this study compared to north Atlantic air masses.